Comentarios bibliográficos - Quintana de Azikri, María Lidia; Cattedra, Olivia; García Bazán, Francisco; B., F.G.; García Daris, Liliana; Gardini, Walter; Manelli, Víctor; Simeone, Cristina; Velloso, Carlos; Victoriano, Sara (Oriente y Occidente, 2022)
.